THERAPEUTIC COMMUNICATION IN REDUCING ELDERLY ANXIETY THROUGH TOUCH THERAPY AT BEKASI HALFWAY HOUSE - Tukino, Tukino (Politeknik Kesejahteraan Sosial Bandung, 2024)
Elderly people undergoing social rehabilitation in halfway houses, especially those experiencing anxiety, need to receive special treatment, including; services to overcome anxiety, and feel optimistic about life lived every day. One technique for dealing with anxiety is touch therapy. This research aims to reveal the application of touch therapy in overcoming anxiety problems experienced by the elderly at the Pedurenan Bekasi Halfway House. The method used is single subject design. Data collection techniques were carried out through interviews and observation. The research results show that applying touch therapy to subjects can reduce anxiety